(untitled) (CIPEEX, 2025)
Cardiovascular diseases are the leading cause of death worldwide, requiring accurate diagnostic methods for early detection, monitoring, and prevention of complications. Tests such as echocardiography, cardiac magnetic resonance imaging (CMR), and coronary angiography are essential. However, cardiac anatomical variations can interfere with the accuracy of these tests, compromising diagnosis. To investigate how variations in cardiac anatomy influence the results of imaging tests used in the diagnosis of cardiovascular diseases and to propose strategies to improve diagnostic accuracy in the face of these changes. A systematic review of the literature was conducted in databases such as PubMed and Google Scholar, with articles from the last 10 years in English and Portuguese. Clinical studies addressing cardiac anatomy and cardiovascular tests were included, excluding publications without anatomical relevance or focusing on non-cardiovascular diseases. Variations such as bicuspid aortic valve, atrial septal aneurysm, and changes in the coronary sinus and pulmonary veins were identified. These anomalies make it difficult to obtain clear images on echocardiography, require specific protocols in CMR, and make catheterization more complex in coronary angiography. The review demonstrated that variations in cardiac anatomy, such as bicuspid aortic valve and atrial septal aneurysm, directly influence the accuracy of c y exams such as echocardiography and angiography. Recognition of these changes is essential to avoid diagnostic errors and improve clinical care. Among the limitations, the methodological diversity of the studies and the scarcity of integrated analyses stand out. In the future, it is important to invest in customized protocols and professional training to improve the accuracy of the exams.